Characterization of the Cystoid Nematode Meloidoderita kirjanovae (Nemata: Sphaeronematidae) from Southern Italy - Vovlas, N. (The Society of Nematologists, 2006)
A population of the cystoid nematode Meloidoderita kirjanovae was detected parasitizing water mint (Mentha aquatica) in southern Italy. The morphological identification of this species was confirmed by molecular analysis using the internal transcribed spacer 1 (ITS1) and 5.8S gene sequences of nuclear ribosomal DNA (rDNA), which clearly separated it from the closely related species Meloidoderita polygoni. A phylogenetic analysis of M. kirjanovae with species of related genera was conducted using sequences of the D2-D3 expansion segments of the 28S nuclear ribosomal RNA gene. The resulting phylogenetic tree was congruent with trees from an extended dataset for Criconematina and Tylenchida. The basal position of the genus Meloidoderita together with Sphaeronema within the Criconematina clade in this tree may indicate their close relationships. The anatomical changes induced by M. kirjanovae population from Italy in water mint were similar to those reported for a nematode population infecting roots of M. longifolia in Israel. Nematode feeding caused the formation of a stellar syncytium that disorganized the pericycle and vascular root tissues.